The moderating effect of gender on the salary equity-affective commitment link: An empirical study of university academic staff in Egypt - Mohamed Hossameldin Khalifa (Cogent Business & Management, 2023)
This study aimed to examine the relationships between perceived internal and external salary equity and affective commitment, as well as the moderation effect of gender on these relationships among university academic staff in Egypt. Structural equation modeling was used to test the study hypotheses, based on data obtained through a face-to-face questionnaire survey of 246 academic staff members conveniently-sampled from eight Egyptian universities located in Greater Cairo. The findings of the study disclose: (1) a significant positive relationship between perceived internal salary equity and affective commitment; (2) a significant positive relationship between perceived external salary equity and affective commitment; and (3) that the relationship between perceived internal salary equity and affective commitment is stronger among males. Despite the fact that this study is, methodologically, a replication of other previous studies, it still contributes new insights from Egypt to the predominantly Western and Asian literature on the perceived salary equity-affective commitment link. Additionally, the study examines the neglected moderation effect of gender on this link.
Keywords: 650; Gender; Affective commitment; Egypt; Perceived equity; Salary